Hidden platforms for cybercrime: experiences investigating darknet services - Ball, Matthew (Fieldwork experiences in criminology and security studies, 2023)
This chapter draws on the authors’ experiences investigating Tor onion service darknet markets and forums (i.e. darknet platforms). These experiences highlight the challenges of investigating ‘hidden’ populations in a universe where the scale, diversity, and locations of actors and services are unknown. Applying cross-disciplinary techniques adapted from the social and computer sciences, we investigate and describe these darknet platforms and draw trends and key observations about these hidden online subcultures.